Advertisement Remove all ads

Prove the Following Trigonometric Identities. (Sec2 θ − 1) (Cosec2 θ − 1) = 1 - Mathematics

Prove the following trigonometric identities.

(sec2 θ − 1) (cosec2 θ − 1) = 1

Advertisement Remove all ads

Solution

We know that

`sec^2 theta - tan^2 theta = 1`

`cosec^2 theta - cot^2 theta = 1`

So,

`(sec^2 theta - 1)(cosec^2 theta - 1) = tan^2 theta xx cot^2 theta`

`= (tan theta xx cot theta)`

`= (tan theta xx 1/tan theta)^2`

`= (1)^2`

=1

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 10 Maths
Chapter 11 Trigonometric Identities
Exercise 11.1 | Q 5 | Page 43
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×